Development of an Educational Game on Quadrilaterals for Grade VII MTS Students - Nurul Laily Fadilah; Arini Hidayati (CV Edujavare Publishing, 2026)
This study aims to develop an educational game on quadrilateral geometry for seventh-grade students of MTs Nurud Da'wah that meets the criteria of validity, practicality, and effectiveness as a learning medium. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included material experts, media experts, a mathematics teacher, and seventh-grade students of MTs Nurud Da'wah. The research instruments consisted of expert validation sheets, student response questionnaires, and learning achievement tests. The results showed that the developed educational game was categorized as valid based on the assessments of material and media experts. Student responses indicated that the learning media was highly practical, easy to use, and engaging. Furthermore, the learning achievement test demonstrated that the educational game was effective, as most students achieved learning mastery after using the game. Therefore, the developed educational game on quadrilateral geometry is feasible to be used as a mathematics learning medium to improve students' understanding and learning motivation.